2022
DOI: 10.3390/su141811166
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: The Impacts of Crude Oil Price Shock on Nigeria’s Economy, Legal and Policy Options

Abstract: The outbreak of the COVID-19 disease has gravely shaken the world economy. The economies of many countries have come under severe strain; Nigeria’s petroleum industry has been particularly affected. This has threatened the countries’ budgets and other essential needs involved in citizens’ welfare. The government is taking drastic measures to combat this scourge, with few results. This study adopts a doctrinal legal research approach and considers both the primary and secondary sources of law, such as judicial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Although the Nigerian government has adopted laws to promote and defend women's rights, no action has been taken, particularly in the area of enhancing or executing those laws, with little progress recorded in areas of public enlightenment. [59][60][61] In fact, domestic violence is still considered a private affair. Thus, law enforcement agencies continue to limit their involvement in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Nigerian government has adopted laws to promote and defend women's rights, no action has been taken, particularly in the area of enhancing or executing those laws, with little progress recorded in areas of public enlightenment. [59][60][61] In fact, domestic violence is still considered a private affair. Thus, law enforcement agencies continue to limit their involvement in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Transparent and clear communication is crucial to inform eligible individuals about the criteria and procedures for accessing COVID-19 palliatives. Improved communication can enhance understanding and increase trust in the distribution system (Olujobi et al , 2022).…”
Section: International Legal Framework Against Corruptionmentioning
confidence: 99%
“…The study revealed a lack of data regarding the distribution and use of funds received from various donors for the COVID-19 emergency response, as well as a dearth of detailed information on the COVID-19 budget or report, including the absence of a transparent tracking system accessible to the public for scrutiny. Corruption within government procurement divisions further compounds the issue, including fraudulent actions related to the acquisition of vaccines and other medical supplies during the pandemic (Olujobi et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Countries like Zimbabwe and Ghana are more dependent on revenue generated, tax (sales and corporate) and tourism earnings (World Bank, 2020). Olujobi et al (2022) purpot that Nigeria's GDP diminished by 6.1% in the second quarter and by 3.62% in the third quarter of 2020 before recovering by 0.1% in 2021. Tax rebates on domestic companies, fee and tax waivers, interest-free loans, debt reliefs and debt deferment reduced the capacity of developing countries to mobilize revenue (Devereux, 2021;Gondwe, 2021).…”
Section: Domestic Resource Mobilisationmentioning
confidence: 99%